Strong Summability of Fourier Transforms at Lebesgue Points and Wiener Amalgam Spaces - Ferenc Weisz (Journal of Function Spaces)
We characterize the set of functions for which strong summability holds at each Lebesgue point. More exactly, if f is in the Wiener amalgam space W(L1,lq)(R) and f is almost everywhere locally bounded, or f∈W(Lp,lq)(R)  (1<p<∞,1≤q<∞), then strong θ-summability holds at each Lebesgue point of f. The analogous results are given for Fourier series, too.